Macroscopically detected female genital injury after consensual and non-consensual vaginal penetration: A prospective comparison study - Lincoln, C.; Perera, R.; Jacobs, Ian; Ward, A. (Churchill Livingstone, 2013)
Objective: The aim of this study was to compare the prevalence, type and pattern of macroscopicallydetected female genital injury after consensual and non-consensual vaginal penetration to further anunderstanding of the forensic significance of genital injury in women reporting sexual assault. A secondaryaim was to identify any effect of a range of possible variables upon the likelihood of genital injuryresulting from vaginal penetrative sexual intercourse.Study design: Two groups of reproductive age women (aged 18e45 years) were prospectively recruitedwithin 72 h of a single episode of vaginal penetrative sex, and macroscopically examined for the presenceof bruises, abrasions and lacerations at twelve external and internal genital sites. Forty one women whopresented for forensic examination after reporting a sexual assault to police were recruited to the nonconsensualgroup and 81 women who presented for routine cervical screening or with sexual healthconcerns to a primary health care service to the consensual group. Each group was examined by adifferent group of doctors, all of whom were experienced in both forensic genital examination andgynaecological examination of healthy and diseased sexually active women. Data collection and examinationprotocols were the same for both groups.Results: The key finding was a statistically significant difference in genital injury prevalence betweenwomen who were vaginally penetrated non-consensually and consensually; 53.7% of the non-consensualgroup (22/41) and 9.9% of the consensual group (8/81) were found to have at least one genital injury [OR10.57, CI (4.07, 27.42), p < 0.00001]. Penetration with finger/s and possible pre-existing genital ‘infection’were found to be significantly associated with the presence of injury in the univariate analysis afteradjusting for consent. Logistic regression demonstrated that women penetrated without consent were19.5 times more likely to sustain at least one genital injury, than those penetrated consensually [OR19.53, CI (6.03, 63.24)] and that a penetration scenario that included finger/s was 4.2 times more likely toresult in at least one genital injury than penetration without finger involvement [OR 4.25, CI (1.42,12.78)], when controlling for other variables in the model. Whilst a comparatively low injury prevalencein the consensual group limited interpretation, results revealed possible differences in genital injurytypology and pattern resulting from non-consensual and consensual vaginal penetration. Lacerationswere seen after both consensual and non-consensual vaginal penetration, while abrasions and bruiseswere seen exclusively in the non-consensual group.Conclusion: This study demonstrated a significant consent group difference in genital injury prevalenceand the highest macroscopically detected genital injury prevalence rate resulting from non-consensualvaginal penetration identified to date. Results also indicate that vaginal penetration with finger/s increasesthe likelihood of sex-related injury. The difference in type of injury sustained as a result of nonconsensualand consensual vaginal penetration was an unexpected finding, and warrants further investigation. These results highlight the importance of a standardised means of detecting genital injurybased on consistent injury definitions, examination protocols, and examiner experience and suggest thatmacroscopic genital examination may be uniquely placed to detect consent group differences in injurytypology and pattern if they exist.